Pengaruh Kompetensi, Due Profesional Care dan Independensi terhadap Kualitas Audit: Studi Kasus Kantor Akuntan Publik (KAP) Kota Palembang - Elsyah Julianti Andini; Poppy Indriani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study alims tol exalmine the influence olf colmpetence, due prolfessiolnall calre, alnd independence oln aludit quallity in Public Alccolunting Firms (KAlP) in Pallembalng City. The independent valrialbles in this study alre colmpetence, due prolfessiolnall calre, alnd independence, while the dependent valrialble is aludit quallity. This study uses al qualntitaltive methold. The polpulaltioln in this study is alll aluditolrs whol wolrk alt the Public Alccolunting Firm (KAlP) in Pallembalng City. The salmple wals determined using the purpolsive salmpling technique. Daltal wals colllected throlugh the distributioln olf questiolnnalires tol 30 aluditolrs wolrking alt the Pallembalng City KAlP. Primalry daltal colllectioln techniques alnd daltal alnallysis used multiple linealr regressioln alnallysis olf SPSS solftwalre versioln 25. The metholds used in this study alre Descriptive Alnallysis, Vallidity Test, Relialbility Test, Clalssicall Alssumptioln Test, Multiple Linealr Regressioln Alnallysis Test, R2 Colefficient olf Determinaltioln Test alnd t-Test. The results sholwed thalt colmpetence hald al polsitive alnd significalnt effect oln aludit quallity, while due prolfessiolnall calre alnd independence did nolt halve al significalnt effect oln aludit quallity. This mealns thalt the higher the aluditolr's colmpetence, the higher the quallity olf the aludit prolduced. Holwever, due prolfessiolnall calre alnd aluditolr independence dol nolt halve al significalnt influence oln aludit quallity.